The effect of age on pulmonary performance using (FEV1/FVC) % as indicator - Hussain, Taghreed A.; Mohammed, Nadiya Y.; Mohammed, Nadiya Y.; Mohammed, Nadiya Y.; Al-Kadi, Ramaq G. W. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: pulmonary function can change with age for normal individual's .Spirometric measurement for the ratio of forced expiratory volume in one second (FEV1), the forced vital capacity and the ratio (FEV1/FVC) can reveal airway obstruction and the consequence change in pulmonary performance. These parameters can be different for different race /ethnic and gender.Methods: Pulmonary function test were carried out on 29normal male and 37 normal female the test parameters were FEV1 and FVC from which the ratio of FEV1/FVC %was calculated in relation to age. Iraqi average for FEV1 and FVC and FEV1/FVC % has also been obtainedResults: results of these tests reveled that the ratio of FEV1/FVC % is almost the same for individual's ages between 20-60 and a significant depression in the value of the ratio FEV1/FVC % for ages > 60 years.Conclusion: the effect may be linked with some changes in the airways in addition to the increased weakness in the muscles in the old age people.